Abdominal Operations without Nasogastric tube :A major advance in modern surgery - Al-Sarraf, Salem A.H.; Al-Obaidi, Safa M.; Al-karim, Muqdad F.A. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Routine use of nasogastric tubes, after abdominal operations, is intended to hasten the return of bowel function, prevent pulmonary complications, diminish the risk ofanastomotic leakage, increase patient comfort and shorten hospital stay. Aim of this study is to evaluate the efficacy of routine nasogastric decompression after abdominal surgery, inachieving each of the above goals.Patients and methods:Two hundred and twelve patients having abdominal operations of any type, emergency and elective have been followed prospectively over a period of three years (1st December 2004 until end of December 2007) in Baghdad teaching hospital. Patients were randomized into two groups. Group 1 had nasogastric tube inserted and kept in place untilintestinal function has returned. Group 2 had no nasogastric tube or immediately removed at the end of the operation. Excluded from the study , were laparoscopic surgeries , gastric andduodenal surgeries.Results: There was earlier return of bowel function and shorter hospital stay in the non tube group. There were no significant statistical differences concerning the occurrence ofpostoperative vomiting, pulmonary complications, anastamotic leakage and wound dehisence.Conclusions: Routine nasogastric decompression does not accomplish any of its intended goals and so should be abandoned in favor of selective use of nasogastric tube.